Angular distributions and angular momentum alignment of O((3)P(J)) atoms formed in the photolysis of O(2)via the Herzberg continuum. - Chestakov, D; van der Zande, W; Parker, D; Vallance, C (Royal Society of Chemistry, 2010)
Sliced velocity-map imaging has been used to measure photofragment scattering distributions for the O((3)P(2)) and O((3)P(1)) products of O(2) photolysis following laser excitation into the Herzberg continuum between 205 and 241 nm. The images were analysed to extract the photofragment spatial anisotropy parameter, β, together with the alignment parameters a(∥), a(⊥), a(⊥), and Re[a(∥, ⊥)]. Our alignment measurements bridge the gap between the recent 193 nm measurement of Brouard et al., Phys. Chem. Chem. Phys., 2006, 8, 5549 and those of Alexander et al., J. Chem. Phys., 2003, 118, 10566 at 222 and 237 nm, and extend out to the threshold at 241 nm. Our measured parameters show no strong dependence on photolysis wavelength. Near the threshold we were able to separate the contributions from the O((3)P(2)) + O((3)P(2)) and O((3)P(2)) + O((3)P(1)) channels, and found significantly different photofragment alignments for the two cases.